Analysis and Design of a 50-kW Two Stage Converters for EV Fast Charger With High Efficiency and Wide Output Voltage of 150–1000 V - Ha-Min Park; Hyung-Woo Lee; Chan-Bae Park; Jae-Bum Lee; Jin-Chul Kim; Ju Lee (IEEE Access)
Generally, the DC-DC converters used in DC fast chargers must cover a wide output voltage with a fixed input voltage, and a single module needs to supply 30-50 kW of power. When designing an LLC resonant converter to cover a wide output voltage with a narrow frequency at high power, a small magnetizing inductance is required, resulting in increased switching turn-off losses. Additionally, a large air gap in the transformer is needed, which increases AC losses in the transformer windings owing to the fringing effect, degrading efficiency. Therefore, to cover a wide output voltage with a fixed input voltage while achieving high power and efficiency, the LLC resonant converter followed by the buck converter is proposed in this paper. Because the LLC resonant converter operates at a fixed frequency, a large magnetizing inductance can be used. This results in lower switching turn-off losses and a smaller air gap in the transformer, which decreases AC losses in the transformer windings. Additionally, by optimally selecting the frequencies of each converter and output voltage of the LLC resonant converter, which functions as the input voltage of the buck converter, high efficiency can be achieved. To confirm the validity of the proposed structure of the DC-DC converter, an 820 V input and 150-1,000 V/50 kW output prototype is built and tested.